From Hotel to Connection: Meningkatkan Komunikasi Global Karyawan Hotel Melalui Bahasa Mandarin di Platinum Hotel Jimbaran Beach Bali - Agustina, Arik; Aprinica, Ini Putu Isha; Dewi, I Gusti Ayu Melistyari; Kesumayathi, Ida Ayu Gayatri; Yanti, Ayu Suwita (Civiliza Publishing, 2025)
Language is used as a means of communication. Through the Mandarin language training program, it is hoped that Mandarin proficiency will improve global communication among hotel employees at Platinum Hotel Jimbaran Beach, Bali. The method implemented is a preliminary study through interviews, material preparation, Mandarin language training, evaluation, and reporting. Participants numbered 30 Platinum Hotel Jimbaran Beach employees, consisting of the Housekeeping, Front Office, F&B Service, Human Resources, Engineering, and Sales & Marketing Departments. Through this program, hotel employees are equipped with foreign language skills, namely Mandarin, which can be used as a medium of communication with tourists at the hotel. The Mandarin language training conducted at Platinum Hotel Jimbaran Beach Bali, successfully improved the basic communication skills of employees in interacting with Mandarin-speaking guests.